IDUâS SOCIOECONOMIC STATUS AND PROBABILITY OF HIV INFECTION IN BANDUNG - Kautsar, Achmad (P2E-LIPI, 2016)
Introduction: Transmission dominance of HIV/AIDS in Indonesia is caused by risky sexual activities and needle sharing behavior. West Java ranks fourth in case of HIV/AIDS among 33 other provinces. Individualâs behavior in performing risky sexual acts or drugs using can be affected by factors of social and economic status.Methods: This research uses cross-sectional survey. The subjects were injecting drug users in Bandung. Sampling is respondent-driven method. This study collects 222 respondents. Collected data were analyzed using logistic regression test. The strength of the effect expressed in odds ratios and marginal effect is used for the interpretation.Results: Individuals who work have marginal effect of -0,2422 (CI, -0,445 to -0,392) smaller than individuals who do not work, income has marginal effect of 0,375 (CI, 0,0928 to 0,657) for income under Rp.500.000,00. Individualâs income between Rp.1.500.000,00-Rp.2.000.000,00 has value of marginal effect is 0,236 (CI, 0,015 to 0,456), and income between Rp.2.000.000,00-Rp.2.500.000,00 has marginal effect of 0,261 (CI, 0,0025 to 0,52). Duration of use syringe has marginal effect of 0,235 (CI, 0,121 to 0,349) higher compared to the duration of use under 12 years.Conclusion: Socioeconomic status can affect the potency of HIV infection. The government should encourage the drug user community to participate in activities which aims to reduce the risk of HIV/AIDS.Â